Interstitial white matter neurons express less reelin and are abnormally distributed in schizophrenia: towards an integration of molecular and morphologic aspects of the neurodevelopmental hypothesis. - Eastwood, S; Harrison, P (2003)
Two main pieces of neurobiological evidence are adduced to support an early neurodevelopmental component to schizophrenia. Firstly, an abnormal distribution of neurons, especially interstitial white matter neurons (IWMNs). Secondly, decreased expression of reelin, a key developmental signalling molecule. Although influential, neither result is wholly established, and a possible link between them has not been examined. We addressed both issues, in superior temporal cortex, in 12 subjects with schizophrenia and 14 controls. The distribution and density of IWMNs, immunostained with the neuronal marker NeuN, was increased in the superficial white matter in schizophrenia (+16%; P=0.03). IWMN density in deep white matter was unaffected. Using in situ hybridization, reelin mRNA was found to be expressed by many IWMNs, layer I neurons, and scattered interneurons. Superficial IWMNs (P=0.008) and layer I neurons (P=0.036) both expressed less reelin mRNA per cell in schizophrenia, with a trend for deep IWMNs (P=0.055). In conclusion, we replicated findings of increased IWMN density, and of decreased reelin expression, in schizophrenia. The loss of reelin reflects, at least partly, its decreased expression by IWMNs. These findings together support neurodevelopmental theories of the disorder, and indicate a link between reelin and IWMNs in this process, consistent with evidence from the heterozygous reeler mutant mouse. The alterations may contribute to the aberrant synaptic connectivity seen in schizophrenia. However, the functional implications of the abnormalities, as well as the mechanisms involved, remain to be fully elucidated.